Sedition and alchemy a biography of John Cale - Mitchell, Tim (Owen, 2002)
This biography of Cale's musical career is revealed as a series of passionate assaults on accepted musical forms and reconstructions of them in his own new shapes, illustrated here by details of his recorded albums and live shows.
Keywords: Cale, John; Rock musicians -- Great Britain -- Biography; Großbritannien; Biografie